2022
DOI: 10.3389/fsurg.2022.853875
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Retrograde Intrarenal Surgery Performed Under Neuraxial vs. General Anesthesia: An Updated Systematic Review and Meta-Analysis

Abstract: BackgroundThe current review aimed to assess if the outcomes of retrograde intrarenal surgery (RIRS) differ with neuraxial anesthesia (NA) or general anesthesia (GA).MethodsThe databases of PubMed, Embase, CENTRAL, ScienceDirect, and Google Scholar were searched up to 3rd December 2021 for randomized controlled trials (RCTs) and observational studies comparing outcomes of RIRS with NA or GA.ResultsThirteen studies involving 2912 patients were included. Eight were RCTs while remaining were observational studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…Nevertheless, both our findings and previous reviews[ 31 32 ] consistently suggest that visceral movements have minimal effect on rates of stone clearance. During NA patients can be instructed to hold their breath, aiding stone disintegration.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Nevertheless, both our findings and previous reviews[ 31 32 ] consistently suggest that visceral movements have minimal effect on rates of stone clearance. During NA patients can be instructed to hold their breath, aiding stone disintegration.…”
Section: Discussionsupporting
confidence: 83%
“…Similar outcomes were observed in a study conducted by Duan et al . [ 31 ] where they compared the results of RIRS accomplished under NA or GA by pooling data from 13 studies, providing more current evidence than previous reviews, which often included only six studies. [ 32 33 ] In their study of primary outcome analysis, involving data from 2,912 patients, they found no significant difference in rates of stone clearance status afterward surgery under NA or GA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this surgical method, kidney stones are treated endourologically with a transureteral approach using flexible ureterenoscopes. Although RIRS is minimally invasive, some complications can develop related to surgery or anesthesia [ 6 , 7 ]. Renal colic, pyelonephritis, hematuria, and acute urinary retention can occur as early complications.…”
Section: Introductionmentioning
confidence: 99%